2021
DOI: 10.21203/rs.3.rs-673695/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Anterior Cruciate Ligament Surgical Reconstruction Through Finite Element Analysis

Abstract: Anterior Cruciate Ligament (ACL) tear is one of the most common knee injuries. The ACL reconstruction surgery aims to restore healthy knee function by replacing the injured ligament with a graft. Proper selection of the optimal surgery parameters is a complex task. To this end, we developed an automated modeling framework that accepts subject-specific geometries and produces finite element knee models incorporating different surgical techniques. Initially, we developed a reference model of the intact knee, val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
(217 reference statements)
0
4
0
Order By: Relevance
“…137 Risvas et al found that increasing the graft pretension and radius could reduce relative knee displacement. 138 Many finite element studies have also been conducted on medial patellofemoral ligament (MPFL) injuries. MPFL reconstruction alone was sufficient to restore the kinematic function of the knee, and tibial tuberosity displacement was necessary when the distance between the tibial tuberosity and the talocrural groove was too large.…”
Section: Ligament Injurymentioning
confidence: 99%
“…137 Risvas et al found that increasing the graft pretension and radius could reduce relative knee displacement. 138 Many finite element studies have also been conducted on medial patellofemoral ligament (MPFL) injuries. MPFL reconstruction alone was sufficient to restore the kinematic function of the knee, and tibial tuberosity displacement was necessary when the distance between the tibial tuberosity and the talocrural groove was too large.…”
Section: Ligament Injurymentioning
confidence: 99%
“…The contact between rigid bodies and soft tissues was assumed to be rigid, and all contacts between two soft tissues were modeled as a sliding elastic contact to enable frictionless sliding and to prevent penetration (Risvas et al, 2022). For the contacts between the tibial and femoral cartilage and the menisci, the femoral cartilage and menisci were assigned as primary surfaces with the tibial cartilage acting as secondary surface.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Combining rigid body dynamics and FEM is also a common route for researchers [15]. Examples of biomechanics application fields using multibody systems are neuromuscular pathologies [16][17][18], study of muscle coordination [19][20][21] and surgery modeling and simulation [22,23].…”
Section: Introductionmentioning
confidence: 99%